Meningkatkan Kemampuan Mengenal Huruf Hijaiyah Melalui Model Pembelajaran Talking Stick Pada Anak Kelompok Bermain - Musfira; Khadijah Khairunisa Adnan; Sri Sufliati Romba (ITEKES Permata Ilmu Maros, 2025)
This study aims to improve the ability to recognize Hijaiyah letters in Group B children through the Talking Stick learning model at RA Al-Adawiyah Kalikur, Lembata Regency, East Nusa Tenggara. The type of research used was classroom action research, which consisted of the stages of planning, implementation, observation, and reflection. The subjects of this study were one teacher and 19 Group B children at RA Al-Adawiyah Kalikur. The object of the research was the application of the Talking Stick learning model to enhance children’s ability to recognize Hijaiyah letters. Data collection techniques employed were observation and documentation, while the data analysis used was descriptive quantitative. The results of the study indicate an improvement in children’s ability to recognize Hijaiyah letters through the Talking Stick learning model in Group B at RA Al-Adawiyah Kalikur. The implementation of Cycle I and Cycle II showed that the children’s recognition ability improved, as reflected in the observation results: 38.25% in Cycle I and 75.5% in Cycle II, which falls under the criteria of Developing as Expected. Thus, it can be concluded that the application of the Talking Stick learning model can effectively improve the ability to recognize Hijaiyah letters in Group B children at RA Al-Adawiyah Kalikur.